Ultrahigh-strength galvanized steel sheet having excellent weldability and method for manufacturing same

By controlling the annealing time and moisture concentration during the annealing process of galvanized steel plates, a single-phase ferrite structure and decarbonization layer is formed, which solves the problem of liquid metal embrittlement during the welding of galvanized steel plates, and improves welding strength and corrosion resistance. performance.

CN119173649APending Publication Date: 2024-12-20HYUNDAE STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095869.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2022-12-05
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing galvanized steel plates are prone to liquid metal embrittlement during welding, resulting in a decrease in welding strength and it is difficult to effectively prevent steel corrosion in a corrosive environment.

Method used

By annealing the cold-rolled steel plate in an annealing furnace, the annealing time and moisture concentration are controlled, a single-phase ferrite microstructure is formed, and a decarbonized layer of 18 μm or more is formed on the surface of the steel plate to inhibit the occurrence of embrittlement of liquid metals.

Benefits of technology

It realizes excellent weldability and high strength of galvanized steel plates, and at the same time effectively prevents steel corrosion in a corrosion environment, expands the welding current range, and reduces the possibility of liquid metal embrittlement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173649A_ABST
    Figure CN119173649A_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability, the method comprising a step of annealing a cold-rolled steel sheet in an annealing furnace, the annealing time (A) and the moisture concentration (B) at which annealing is performed in the annealing furnace are controlled on the basis of the product of the positive square root (A1 / 2) of the annealing time and the natural logarithm value (ln (1 / B)) of the reciprocal value of the moisture concentration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel plate and a method for manufacturing the same, and more particularly to an ultra-high strength galvanized steel plate with excellent weldability and a method for manufacturing the same. Background Art

[0002] The automotive industry is focusing on improving fuel efficiency and reducing weight to meet the demands of the times such as resource depletion, rapid global warming and high oil prices. Moreover, as regulations on passenger safety are gradually strengthened, ultra-high strength steel is required. In addition, various improvements are required for galvanized steel sheets with excellent sacrificial properties to prevent corrosion of steel by pre-dissolving low-potential zinc when exposed to a corrosive environment. For example, there is a growing demand for improving the liquid metal embrittlement (LME) problem, which is the embrittlement caused by the melting of the galvanized layer during the spot welding process in the automobile assembly line and the penetration of the molten metal zinc to the interface of the residual austenite present in the surface layer of the base steel.

[0003] As a related document, there is Korean Patent Application Publication No. 20200075949A. Summary of the invention

[0004] Technical issues

[0005] Therefore, the present invention has been completed in view of the above-mentioned problems, and one object of the present invention is to provide an ultra-high strength galvanized steel sheet with excellent weldability and a method for manufacturing the same.

[0006] It should be understood that the technical problems are only provided as examples, and the technical ideas of the present invention are not limited thereto.

[0007] Technical Solution

[0008] According to one aspect of the present invention, the above and other objects can be achieved by providing a method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability, the method comprising: annealing a cold-rolled steel sheet in an annealing furnace, wherein the positive square root of the annealing time (A) is 1 / 2 ) and the natural logarithm of the inverse of the moisture concentration (ln(1 / B)) to control the annealing time (A) and moisture concentration (B) in the annealing furnace.

[0009] In the method for producing an ultra-high strength galvanized steel sheet having excellent weldability, annealing can be controlled so that the moisture concentration (B) in the annealing furnace increases as the annealing time (A) for annealing becomes shorter.

[0010] In the method for producing an ultra-high strength galvanized steel sheet having excellent weldability, annealing may be controlled so that the annealing time (A) for annealing increases as the moisture concentration (B) in the annealing furnace becomes lower.

[0011] In the manufacturing method of the ultra-high strength galvanized steel sheet with excellent weldability, the cold-rolled steel sheet may contain, in weight%, carbon (C): 0.1 weight % to 0.5 weight %; silicon (Si): 1.0 weight % to 3.0 weight %; manganese (Mn): 1.5 weight % to 3.5 weight %; phosphorus (P): greater than 0 weight % and less than or equal to 0.02 weight %; sulfur (S): greater than 0 weight % and less than or equal to 0.01 weight %; aluminum (Al): greater than 0 weight % and less than or equal to 0.1 weight %; nitrogen (N): greater than 0 weight % and less than or equal to 0.01 weight %, and the rest is Fe and other inevitable impurities.

[0012] In the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability, annealing can be performed at a temperature corresponding to the dual-phase range of austenite and ferrite, and the annealing can cause a decarburization reaction on the surface of the steel sheet, so that the annealing can include transforming the austenite present in the surface layer of the steel sheet into ferrite.

[0013] In the method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability, annealing may be performed at an annealing temperature of 830°C to 900°C.

[0014] In the method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability, annealing can be performed under the condition that the annealing time (A) and the moisture concentration (B) in the annealing furnace satisfy the following formula 1. Here, the unit of the annealing time (A) is second (s), and the unit of the moisture concentration (B) in the annealing furnace is ppm.

[0015] <Formula 1>

[0016] (A) 1 / 2 x ln(1 / B)≤-65

[0017] The method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability may further include: after annealing, initially cooling the steel sheet to a temperature of 600°C or higher and less than 800°C at an average cooling rate of 1 to 20°C / s; secondarily cooling the steel sheet to a temperature of 200°C or higher and less than 300°C at an average cooling rate of 20°C / s or greater; reheating the steel sheet to 350°C to 490°C and maintaining for 100 seconds or less; and galvanizing the steel sheet.

[0018] In the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability, a single-phase ferrite microstructure can be formed on the surface layer of the steel sheet after galvanizing, and the thickness of the decarburized layer formed on the surface layer of the steel sheet can be 18 μm or greater.

[0019] In the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability, the applicable welding current range of the galvanized steel sheet can be 6.0 kA to 7.5 kA.

[0020] According to another aspect of the present invention, there is provided an ultra-high strength galvanized steel sheet with excellent weldability, comprising a base steel, wherein the base steel comprises, by weight%, carbon (C): 0.1 weight % to 0.5 weight %; silicon (Si): 1.0 weight % to 3.0 weight %; manganese (Mn): 1.5 weight % to 3.5 weight %; phosphorus (P): greater than 0 weight % and less than or equal to 0.02 weight %; sulfur (S): greater than 0 weight % and less than or equal to 0.01 weight %; aluminum (Al): greater than 0 weight % and less than or equal to 0.1 wt. %; Nitrogen (N): greater than 0 wt. % and less than or equal to 0.01 wt. %, and the rest is Fe and other inevitable impurities; and a galvanized layer formed on the base steel, wherein a single-phase ferrite microstructure is formed on the surface layer of the base steel in contact with the galvanized layer, and a thickness of the decarburized layer formed on the surface layer of the base steel is 18 μm or greater, wherein the microstructure of the base steel includes 0% to 40% ferrite, 10% to 30% residual austenite, and the rest is martensite.

[0021] In ultra-high strength galvanized steel sheets with excellent weldability, the applicable welding current range of the galvanized steel sheets can be 6.0 kA to 7.5 kA, and when welding galvanized steel sheets, the possibility of liquid metal embrittlement (LME) (i.e., the zinc coating melts and penetrates into the surface of the base steel, causing embrittlement) can be 0%.

[0022] Beneficial Effects

[0023] According to the present invention, an ultra-high strength galvanized steel sheet having excellent weldability and a method for producing the same can be realized.

[0024] The effects of the present invention are described only as examples, and the scope of the present invention is not limited to these effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a flowchart showing a method for manufacturing an ultra-high strength galvanized steel sheet according to an embodiment of the present invention.

[0026] Figure 2 A subsequent heat treatment (annealing, cooling, reheating) step applied to a cold-rolled steel sheet in a method for producing an ultra-high strength galvanized steel sheet having excellent weldability according to an embodiment of the present invention is shown.

[0027] Figure 3 A photograph showing the appearance of liquid metal embrittlement cracks occurring in a galvanized steel sheet as a comparative example of the present invention is shown.

[0028] Figure 4 An outline of a decarburization reaction in a method for producing an ultra-high strength galvanized steel sheet according to an embodiment of the present invention is shown.

[0029] Figures 5 to 7 The figures respectively show the cross section of the steel surface layer, the elongation test evaluation results and the photographs of the occurrence of liquid metal embrittlement (LME) cracks under the conditions of 800°C Grabe test temperature and normal dew point (DP<-45°C) in the first experimental embodiment of the present invention.

[0030] Figures 8 to 10 are photographs showing the cross section of steel, the elongation test evaluation results and the occurrence of liquid metal embrittlement (LME) cracks under the conditions of 800°C Grabe test temperature and high dew point (DP 0°C) in the first experimental example of the present invention.

[0031] Fig.11 The positive square root (A) of the annealing time (A) in the annealing furnace according to the second experimental embodiment of the present invention is shown. 1 / 2 ) multiplied by the natural logarithm of the reciprocal of the water concentration (B) (ln(1 / B)).

[0032] Fig.12 The graph shows the thickness of the decarburized layer formed on the surface layer of the base steel according to the second experimental example of the present invention, depending on the annealing time (A) and the moisture concentration (B) in the annealing furnace.

[0033] Fig.13 The graph shows the variation of the liquid metal embrittlement (LME) occurrence rate with annealing time (A) and water concentration (B) in the annealing furnace according to the second experimental example of the present invention.

[0034] Fig.14 The results of applying the spot welding process according to the third experimental example are shown. DETAILED DESCRIPTION

[0035] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. The embodiments of the present invention are provided to explain the technical idea of ​​the present invention more completely to those skilled in the art, and the following embodiments may be modified in many different forms, but the scope of the technical idea of ​​the present invention is not limited to the following embodiments. On the contrary, the embodiments are provided to make the present invention thorough and complete, and to fully convey the technical idea of ​​the present invention to those skilled in the art. The same reference numerals in the specification represent the same elements. In addition, various elements and regions are schematically drawn in the accompanying drawings. Therefore, the technical idea of ​​the present invention is not limited by the relative sizes or spacings drawn in the accompanying drawings.

[0036] Figure 1 is a flowchart showing a method for manufacturing an ultra-high strength galvanized steel sheet according to an embodiment of the present invention.

[0037] Reference Figure 1The method for manufacturing an ultra-high strength galvanized steel sheet according to an embodiment of the present invention includes a step of supplying steel (S10), a step of hot rolling the steel to form a hot-rolled steel sheet (S20), a step of cold rolling the hot-rolled steel sheet to form a cold-rolled steel sheet (S30), a step of annealing the cold-rolled steel sheet (S40), a step of primary cooling and secondary cooling the annealed steel sheet (S50, S60), a step of reheating the cooled steel sheet (S70), and a step of galvanizing the steel sheet (S80).

[0038] The method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to the technical concept of the present invention comprises a step of annealing the cold-rolled steel sheet in an annealing furnace (S40), wherein the positive square root of the annealing time (A 1 / 2 ) and the natural logarithm of the inverse value of the water concentration (ln(1 / B)) to control the annealing time (A) and the water concentration (B) in the annealing furnace. For example, the annealing step (S40) can be performed under the condition that the annealing time (A) and the water concentration (B) in the annealing furnace satisfy the following formula 1:

[0039] <Formula 1>

[0040] (A) 1 / 2 x ln(1 / B)≤K (where K is a predetermined constant value)

[0041] As an example of a method for producing an ultra-high strength galvanized steel sheet having excellent weldability, annealing may be controlled so that the moisture concentration (B) in the annealing furnace increases as the annealing time (A) for which the annealing is performed becomes shorter.

[0042] As another example of a method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability, annealing may be controlled such that the annealing time (A) for which annealing is performed increases as the moisture concentration (B) in the annealing furnace becomes lower.

[0043] According to this configuration, when the galvanized steel sheet is welded, the galvanized layer melts and penetrates the surface of the base steel, thereby suppressing the occurrence of liquid metal embrittlement (LME), and the thickness of the decarburized layer formed on the steel sheet surface can be 18 μm or more.

[0044] The present invention is not limited to the superficial understanding of alleviating liquid metal embrittlement (LME) when the hardness of the surface layer is reduced due to surface decarburization, but recognizes the problem that it is difficult to optimize the decarburized layer only by the dew point in the annealing furnace, and discloses a technical idea of ​​comprehensively considering the annealing time and dew point according to the annealing temperature to ensure the optimal decarburization conditions.

[0045] Hereinafter, a method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability according to an embodiment of the present invention is described in detail.

[0046] Steel providing step (S10)

[0047] Recently, the automotive industry has become increasingly interested in lightweight car bodies using ultra-high-strength steels to simultaneously meet crash safety and fuel efficiency regulations. In the steel industry, research and development of ultra-high-strength steels are being actively conducted to meet the needs of customer automakers. The quenching and partitioning (Q&P) heat treatment technology developed to simultaneously ensure high strength and high ductility of automotive steels suppresses the formation of carbon precipitates from carbon released from the martensitic structure during quenching, and diffuses carbon into the retained austenitic structure through partitioning. Through the redispersion of carbon, the retained austenitic structure is stable even at room temperature, ultimately ensuring both high ductility due to the retained austenitic structure and high strength due to the martensitic structure.

[0048] Compared with ordinary steels, these Q&P steel plates contain a large amount of substitutional solid solution alloying elements, such as silicon (Si) and aluminum (Al), which can inhibit the movement of iron (Fe) atoms and thus inhibit the formation of carbide precipitates within the structure; these Q&P steel plates also contain a large amount of austenite stabilizing alloying elements, such as carbon (C) and manganese (Mn), to increase the volume fraction of the stable retained austenite structure and improve deformation induced plasticity (TRIP) properties.

[0049] Meanwhile, it is obvious that the technical idea of ​​the present invention can be applied to the above-mentioned Q&P steel plate, but it is obvious that the technical idea of ​​the present invention can be widely applied to various steel plates and is not limited to the application of Q&P steel plates.

[0050] Hereinafter, the functions and contents of exemplary components contained in the ultra-high strength cold-rolled steel sheet according to the embodiment of the present invention are described. Here, the contents of the component elements are all referred to as "weight %".

[0051] Carbon (C): 0.1 to 0.5%

[0052] Carbon is the most important alloying element in steelmaking, and its main purpose is to play a basic strengthening role and stabilize austenite. A high carbon concentration in austenite can improve the stability of austenite, making it easy to ensure appropriate austenite for material improvement. A high carbon concentration in austenite can improve the stability of austenite, making it easy to ensure appropriate austenite for material improvement. When the carbon content is less than 0.1%, it is difficult to ensure the desired yield strength and elongation. When the carbon content is more than 0.5%, weldability may decrease due to an increase in carbon equivalent. Therefore, it is preferred that the carbon content is 0.1% to 0.5% of the total weight of the steel plate.

[0053] Silicon (Si): 1.0 to 3.0%

[0054] Silicon is an important factor in inhibiting the formation of carbides (such as Fe 3C) forming element, which increases the activity of carbon and thus increases the diffusion rate of austenite. As is well known, silicon is a ferrite stabilizing element and an element that increases ductility by increasing the ferrite fraction during cooling. When the silicon content is less than 1.0%, the effect of adding silicon is insufficient. When the silicon content exceeds 3.0%, oxides (SiO 2 ), which may cause the wettability of the corresponding part to decrease, thereby reducing the plating performance. Therefore, the content of silicon is preferably 1.0 to 3.0% based on the total weight of the steel sheet.

[0055] Manganese (Mn): 1.5% to 3.5%

[0056] Manganese is an austenite stabilizing element. With the addition of manganese, the martensitic transformation starting temperature Ms gradually decreases, which may result in an effect of increasing the amount of retained austenite during the continuous annealing heat treatment process. When the manganese content is less than 1.5%, the effect of adding manganese is insufficient. When the manganese content is greater than 3.5%, the carbon equivalent increases, significantly reducing weldability. In addition, during the process, oxides (MnO) are formed on the surface of the steel sheet, which may result in a decrease in wettability of this part, thereby reducing the plating performance. Therefore, based on the total weight of the steel sheet, the manganese content is preferably 1.5% to 3.5%.

[0057] Phosphorus (P): greater than 0% and Less than or equal to 0.02%

[0058] Phosphorus can play a role similar to silicon in steel. However, when phosphorus is added in excess of 0.02% of the total weight of the steel plate, it may reduce the weldability of the steel plate and increase brittleness, which may lead to material degradation. Therefore, it is preferred to limit the phosphorus content to greater than 0% and less than or equal to 0.02% of the total weight of the steel plate.

[0059] Sulfur (S): greater than 0% and Less than or equal to 0.01%

[0060] Sulfur is an element inevitably contained in steel production, which combines with manganese (Mn) to form MnS, thereby inhibiting the toughness and weldability of steel and reducing the corrosion resistance and impact characteristics of steel. Therefore, it is preferred to limit the sulfur content to more than 0% and less than or equal to 0.01% of the total weight of the steel plate.

[0061] Aluminum (Al): greater than 0% and Less than or equal to 0.1%

[0062] Aluminum (Al) has a similar effect to silicon (Si), mainly playing the role of strengthening the solid solution and inhibiting the formation of carbides. It is an element added mainly for deoxidation, inhibiting the formation of carbides to effectively form a residual austenite phase and improving the strength-elongation balance. When the content of aluminum (Al) is greater than 0.1%, the workability of the steel sheet may deteriorate due to the increase of inclusions such as aluminum oxide. Therefore, the addition of aluminum (Al) is preferably 0.1% or less of the total weight of the steel sheet.

[0063] Nitrogen (N): greater than 0% and Less than or equal to 0.01%

[0064] Nitrogen (N) is an element that deteriorates aging resistance, and when the amount of nitrogen exceeds 0.01%, the aging resistance deteriorates significantly. In addition, nitrogen (N) combines with boron (B) to form BN and consumes boron (B). Therefore, nitrogen (N) reduces the hardenability due to the solid solution boron (B), making it difficult to ensure a tempered martensite phase with a predetermined area ratio. In addition, nitrogen (N) exists as an impurity element in ferrite and reduces ductility through deformation aging. Therefore, the content of nitrogen (N) is preferably lower. Therefore, it is preferred to limit the content of nitrogen (N) to greater than 0% and less than or equal to 0.01% of the total weight of the steel plate.

[0065] Meanwhile, in addition to the above composition, the ultra-high strength cold-rolled steel sheet according to the embodiment of the present invention may further selectively include any combination of the following components.

[0066] At least one of titanium (Ti), niobium (Nb) and vanadium (V): greater than 0% and Less than or equal to 0.1%

[0067] Titanium (Ti), niobium (Nb) and vanadium (V) elements are the main elements precipitated in the form of carbides in steel. The purpose of the present invention is to ensure the stability of residual austenite and improve strength by refining the original austenite grains caused by the formation of precipitates, and to achieve precipitation hardening by refining the ferrite grains and the presence of precipitates in the ferrite. That is, they are combined with carbon (C) or nitrogen (N) to precipitate in the form of NbC, NbN, TiC, TiN, VC or VN, or improve the strength of the steel plate by strengthening the solid solution in iron (Fe). For example, titanium (Ti) effectively improves strength by forming carbonitrides or sulfides, and suppresses the formation of boron nitride (BN) by precipitating titanium nitride (TiN) in combination with nitrogen, so titanium (Ti) can effectively express the quenching performance of boron (B). Niobium (Nb) is an element that helps to improve the strength of the base material by combining with carbon (C) to form a precipitation strengthening effect of NbC precipitates when added in small amounts. Like niobium (Nb), vanadium (V) is added as a strengthening element.

[0068] When the sum of the above elements exceeds 0.1% of the entire steel plate, in addition to increasing the manufacturing cost, excessive precipitates may be generated in the ferrite phase, which may lead to excessive precipitation strengthening, reduce the elongation of the steel plate, and cause low-temperature toughness and weldability to deteriorate due to a large amount of precipitates. Therefore, it is limited to less than or equal to 0.1%.

[0069] Chromium (Cr): greater than 0% and Less than or equal to 0.8%

[0070] Chromium (Cr) is an element with high hardenability, and is added to improve strength by transformation strengthening. However, when chromium (Cr) exceeds 0.8 wt%, an upper bainite-like structure is formed, which makes the overall structure uneven, thereby reducing toughness. Therefore, it is preferred to control the content to be less than or equal to 0.8 wt%.

[0071] Molybdenum (Mo): greater than 0% and Less than or equal to 0.5%

[0072] Molybdenum (Mo) is an element with higher hardenability than the above-mentioned chromium (Cr), and is added to improve strength by transformation strengthening. When it exceeds 0.5 wt % within the carbon (C) component range of the present invention, a large amount of light secondary phases such as martensite / austenite (MA) phases are formed, which reduces toughness. Therefore, it is preferred to control the content to 0.5 wt %.

[0073] The remaining component of the ultra-high strength cold rolled steel sheet is iron (Fe). However, since unexpected impurities are inevitably added from raw materials or the surrounding environment during the normal steelmaking process, they cannot be excluded. Since these impurities are well known to technicians in the manufacturing field, they are not specifically mentioned in this specification.

[0074] In the manufacturing method according to the present invention, the semi-finished product as the target of the hot rolling process and the cold rolling process may be, for example, a slab. The slab in the semi-finished state may be obtained by a continuous casting process after obtaining molten steel of a predetermined composition by a steelmaking process.

[0075] Hot rolling step (S20)

[0076] The step (S20) of forming a hot rolled steel sheet by performing a hot rolling process on steel is performed.

[0077] Since the steel is high alloy steel, edge burst and rolling load need to be minimized to ensure mass production, so the rolling finish temperature and coiling temperature can be set in a high temperature range.

[0078] The steel is reheated at a temperature of Ac3 or higher, for example, at a slab reheating temperature (SRT) in the range of 1150°C to 1250°C. By this reheating, redissolution of segregated components and redissolution of precipitates may occur during the casting process. When the reheating temperature is lower than 1150°C, a problem of rapid increase in hot rolling load may occur. If the reheating temperature exceeds 1250°C, it may be difficult to load and remove the slab from the heating furnace due to bending, and it may be difficult to ensure the strength of the finally produced steel plate due to coarsening of the original austenite grains. The reheating temperature may vary depending on the steel.

[0079] Next, the reheated steel is hot rolled. Hot rolling may be performed at a finishing outlet temperature (FDT) of, for example, 850°C to 1000°C. When the FDT is higher than 1000°C, there is a concern that the quality of the steel sheet may deteriorate due to the presence of surface scale on the steel sheet. In addition, when the FDT is lower than 850°C, an increase in rolling load and a decrease in productivity may result. The finishing outlet temperature may vary depending on the steel.

[0080] Next, the hot rolled steel is cooled at a cooling rate of 10 to 30°C / s and then coiled at a coiling temperature (CT) of, for example, 500°C to 700°C. The coiling temperature may vary depending on the steel. When the coiling temperature is higher than 700°C, an unwanted internal oxide layer may be generated in the hot rolled steel sheet or the coiled hot rolled coil. Since the internal oxidation of the coiled hot rolled coil thus has a deviation, it is difficult to uniformly control the thickness of the internal oxide layer. When the coiling temperature is lower than 500°C, an undesirable low temperature structure may be formed.

[0081] Cold rolling step (S30)

[0082] The step (S30) of forming a cold-rolled steel sheet by applying a cold rolling process to the hot-rolled steel sheet is performed.

[0083] Meanwhile, in the method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability according to an embodiment of the present invention, a softening heat treatment step and a pickling step may be sequentially performed before performing a cold rolling process.

[0084] In the softening heat treatment step, the hot-rolled steel sheet is subjected to a softening heat treatment to achieve material softening, thereby alleviating the reduction rate load problem and shape defect problem in the subsequent cold rolling process. That is, the softening heat treatment can ensure the cold rolling performance by softening the hot-rolled steel sheet through the softening heat treatment to improve the efficiency of the cold rolling operation. When the strength of the hot-rolled steel sheet is high, problems such as thickness fluctuation and shape defects may occur during the cold rolling process. However, in the case of the ultra-high strength steel softening heat treatment process according to the present invention, it is applied to a hot-rolled coil with residual oxide scale, not a cold-rolled coil, so it is necessary to take countermeasures against the change in surface characteristics caused by the high-temperature reaction of the oxide scale during the softening heat treatment process. Generally, it is known that in the case of ultra-high strength steel containing a large amount of Si and Mn in the type of steel, internal oxides are generated along the grain boundaries of the base steel at high temperatures together with the oxide scale. Since the main component of the matrix is ​​Fe, the pickling performance of the oxide layer formed by internal oxidation is poor. Therefore, there is a problem that the same pickling time as that of a general hot-rolled steel sheet cannot completely remove the internal oxide layer, and a long pickling time is required, which reduces productivity. This internal oxidation occurs when the activity of easily oxidizable elements such as Si and Mn is high and is present under specific oxygen partial pressure conditions. Therefore, when a hot rolled coil with residual scale is heat treated in a high temperature reducing gas atmosphere, additional internal oxidation occurs due to the oxygen generated during the scale reduction reaction. Internal oxides, which are not observed in hot rolled steel, develop unevenly over the entire coil length after the softening heat treatment, and the scale reduction and internal oxidation development behaviors may differ depending on the position within the coiled coil. In the case of an outer coil subjected to a softening heat treatment, internal oxidation growth due to the scale hydrogen reduction reaction is mainly observed, while in the case of an inner coil, internal oxidation growth due to the scale eutectoid reaction (4FeO→4Fe+2O 2) and resulting in internal oxidation growth. This difference in internal oxidation growth behavior is determined to be due to the fact that the ease of penetration of the reaction gas depends on the different positions of the coiled coil, and it can be understood that during the softening heat treatment, the oxygen produced by the hydrogen reduction of the oxide scale and the eutectic reaction diffuses into the base material and serves as an internal oxidation reaction material. Since the internal oxide layer is preferably formed as uniformly as possible on the entire steel plate, it is preferred to suppress the internal oxide layer as much as possible in the coiling step and form the internal oxide layer in the softening heat treatment. Taking these aspects into consideration, in the method for manufacturing an ultra-high strength cold-rolled steel sheet of the present invention, the coiling temperature is adjusted to 500°C to 700°C, and the softening heat treatment temperature is adjusted to 500°C to 650°C. The softening heat treatment can be performed in a batch annealing furnace (BAF) when the hot-rolled steel sheet is coiled, and can be performed in a hydrogen atmosphere. The hot-rolled steel sheet that has undergone softening heat treatment under process conditions can ensure cold rolling performance because its material is softened. In addition, since the inner oxide layer formed by the softening heat treatment has a predetermined thickness (for example, a thickness of 10 μm or less), the subsequent pickling performance can be ensured at the same time.

[0085] When the softening heat treatment is performed at a temperature of 500°C or lower, the softening degree of the material of the hot-rolled steel sheet subjected to the softening heat treatment is too small to ensure the subsequent cold rolling performance. That is, when the softening heat treatment is performed, austenite is excessively formed, and martensite is formed during cooling, so the strength reduction may not be effectively exhibited.

[0086] In addition, when the softening heat treatment is performed at a temperature exceeding 650° C., the thickness of the internal oxide layer formed by the softening heat treatment exceeds 10 μm, making it difficult to ensure subsequent pickling performance.

[0087] Meanwhile, in the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to an embodiment of the present invention, whether to apply the softening heat treatment step can be selected according to the type of steel or the target strength. For example, if the target tensile strength after cold rolling / annealing is 1180 MPa or more, the softening heat treatment step can be performed, and if the target tensile strength after cold rolling / annealing is 980 MPa, the softening heat treatment step may not be performed. The time for performing the softening heat treatment can be 1 to 12 hours.

[0088] In the pickling treatment step, the hot rolled steel sheet may be pickled with an acid after the softening heat treatment. The hot rolled steel sheet may be pickled to remove at least a portion of the internal oxide layer. The pickling treatment may be performed, for example, at a temperature of 70° C. to 90° C. and a hydrochloric acid concentration of 5% to 15% for 20 to 40 seconds. In addition, an inhibitor concentration of 0.1% to 0.5% may be used.

[0089] In the cold-rolled steel sheet forming step (S30), the pickled hot-rolled steel sheet may be cold-rolled at an average reduction rate of, for example, 40% to 60% and a pressing force of, for example, 700 tons to 1800 tons, thereby producing a cold-rolled steel sheet. The microstructure of the cold-rolled steel sheet has a shape that is an extension of the structure of the hot-rolled steel sheet, and the microstructure of the finally manufactured steel sheet is determined by subsequent heat treatment.

[0090] Figure 2 A subsequent heat treatment (annealing, cooling, reheating) step applied to a cold-rolled steel sheet in a method for producing an ultra-high strength galvanized steel sheet having excellent weldability according to an embodiment of the present invention is shown.

[0091] Annealing step (S40)

[0092] Reference Figure 2 , the cold rolled steel sheet is annealed in a continuous annealing furnace with a normal slow cooling section. The annealing heat treatment can be performed at a temperature corresponding to the dual phase range of austenite and ferrite. By heat treating in the dual phase region, the appropriate ferrite fraction can be ensured, and the ideal ferrite, tempered martensite and retained austenite can be achieved in the final microstructure, thereby obtaining the target steel sheet material.

[0093] The annealing heat treatment temperature and annealing time affect the austenite grain size and can therefore have a large impact on the strength of the cold rolled steel sheet. The annealing heat treatment is performed at a heating rate of, for example, 1°C / s or more, for example, at a heating rate in the range of 1°C / s to 15°C / s. When the heating rate is less than 1°C / s, it takes a long time to reach the target annealing temperature, which reduces production efficiency and may increase the grain size. The annealing heat treatment can be performed, for example, at a temperature of Ae1 or more, for example, at a temperature in the range of 830°C to 900°C.

[0094] Meanwhile, as the annealing time (ie, the time for which the annealing heat treatment is performed) increases, it affects the coarsening due to the growth of austenite grains as well as the annealing heat treatment temperature.

[0095] The present invention confirms that by controlling the annealing time (A) for annealing and the moisture concentration (B) in the annealing furnace, the possibility of liquid metal embrittlement (LME) (embrittlement caused by the melting and penetration of the zinc coating into the surface of the base steel during the welding process of the galvanized steel sheet) can be suppressed, and the thickness of the decarburized layer formed on the surface of the steel sheet can be controlled.

[0096] Specifically, the square root of the annealing time (A 1 / 2) and the natural logarithm of the inverse value of the water concentration (ln(1 / B)) to control the annealing time (A) and the water concentration (B) in the annealing furnace. For example, the annealing step (S40) can be performed under the condition that the annealing time (A) and the water concentration (B) in the annealing furnace satisfy the following formula 1:

[0097] <Formula 1>

[0098] (A) 1 / 2 x ln(1 / B)≤K (where K is a predetermined constant value)

[0099] As an example of a method for producing an ultra-high strength galvanized steel sheet having excellent weldability, annealing may be controlled so that the moisture concentration (B) in the annealing furnace increases as the annealing time (A) for which the annealing is performed becomes shorter.

[0100] As another example of a method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability, annealing may be controlled such that the annealing time (A) for which annealing is performed increases as the moisture concentration (B) in the annealing furnace becomes lower.

[0101] According to this configuration, the possibility of liquid metal embrittlement (LME) (embrittlement caused by the galvanized layer melting and penetrating into the base steel surface when welding galvanized steel sheets) can be suppressed, and the thickness of the decarburized layer formed on the surface layer of the steel sheet can be 18 μm or greater.

[0102] Primary cooling and secondary cooling steps (S50, S60)

[0103] The annealed cold-rolled steel sheet is cooled multiple times. Specifically, a primary cooling step (S50) of the annealed steel sheet and a secondary cooling step (S60) of the annealed steel sheet may be performed.

[0104] Step (S50), i.e., primary cooling the steel plate to a temperature of 600°C or higher and lower than 800°C at an average cooling rate of 1 to 20°C / s, is a slow cooling step, which attempts to ensure that a certain amount of ferrite is contained in the final microstructure during the heat treatment process, thereby ensuring the plasticity of the final microstructure. When the cooling end temperature of the slow cooling is lower than 600°C, an undesirable amount of ferrite transformation may occur, which may reduce strength.

[0105] Next, step (S60), i.e., secondary cooling the annealed steel sheet to 200°C or higher and lower than 300°C at an average cooling rate of 20°C / s or more, preferably 50°C / s or more, is a rapid cooling step. By controlling the rapid cooling end temperature after slow cooling, the final material can be easily ensured by transforming austenite in the microstructure into martensite, and an average cooling rate of 20°C / s or more is required to suppress phase transformation that may occur during the rapid cooling process.

[0106] Next, the secondary cooled cold rolled steel sheet may be maintained at a secondary cooling end temperature of 200° C. or higher and less than 300° C. for a period of, for example, 1 second to 100 seconds. During the holding time after rapid cooling, first, the steel may be subjected to a temperature homogenization treatment. The secondary cooling end temperature may be a martensitic transformation start temperature (Mt). s ) and martensitic transformation completion temperature (M f ) between the temperatures.

[0107] Next, while the temperature is isothermally maintained at the secondary cooling end temperature, some of the retained austenite may transform to lower bainite, etc.

[0108] Reheating step (S70)

[0109] The cold-rolled steel sheet after multiple cooling can be reheated at a heating rate of, for example, 1°C / s to 50°C / s, and maintained at a temperature range of, for example, 350°C to 490°C for 100 seconds or less for partitioning heat treatment. The partitioning heat treatment temperature may be higher than the martensite transformation start temperature (Ms). The purpose of the reheating process is to ensure strength and elongation through carbon enrichment in the retained austenite and martensite tempering during the process, and ultimately maintain the final microstructure composition.

[0110] If the partitioning heat treatment temperature is lower than 350°C, the partitioning effect may be insufficient. If the partitioning heat treatment temperature exceeds 490°C, the size of the carbides may become coarser and the strength may decrease. Compared with the partitioning temperature, the partitioning heat treatment holding time may have a smaller effect. If the partitioning heat treatment holding time exceeds 100 seconds, the heat treatment efficiency may decrease, the carbide size may increase, and the strength may decrease. The partitioning heat treatment step can be performed immediately after the above-mentioned multiple coolings, or after keeping at room temperature for a few minutes or longer. In the case of non-plated materials, after the partitioning heat treatment step is completed, it is cooled to room temperature, for example, to a temperature in the range of 0°C to 40°C.

[0111] The multiple cooling steps (S50, S60) and the reheating step (S70) correspond to the quenching and partitioning (Q&P) heat treatment step developed to simultaneously ensure high strength and high ductility of the steel material. It is a technology that can suppress the carbon released from the martensite structure during the quenching process from forming carbon precipitates and allow carbon to diffuse into the retained austenite structure through partitioning. Through the redispersion of carbon, the retained austenite structure can be stabilized even at room temperature, and ultimately, high ductility due to the retained austenite structure and high strength due to the martensite structure can be ensured.

[0112] Galvanizing step (S80)

[0113] Step (GI) may be performed and step (GA) may be further performed, wherein the annealed cold-rolled steel sheet is immersed in a molten galvanizing bath for molten galvanizing to form a molten galvanized steel sheet, and step (GA) is performed to perform heat treatment to alloy the cold-rolled steel sheet and the molten galvanized steel sheet (on which a molten galvanized layer is formed) to form an alloyed molten galvanized steel sheet.

[0114] After the partitioning heat treatment step, the plated material can directly enter the plating bath without cooling to room temperature.

[0115] The inlet temperature of the plating bath may be, for example, 460°C, and the plating bath may be a zinc plating bath containing 0.11 to 0.22 wt% aluminum and saturated Fe. Alternatively, the plating bath may be a Zn-Mg-Al plating bath. Meanwhile, the heat treatment temperature for alloying may be 450 to 600°C.

[0116] The ultra-high strength galvanized steel sheet with excellent weldability according to the embodiment of the present invention achieved by performing the above steps may include a base steel, which includes, in terms of weight %, for example, carbon (C): 0.1 weight % to 0.5 weight %; silicon (Si): 1.0 weight % to 3.0 weight %; manganese (Mn): 1.5 weight % to 3.5 weight %; phosphorus (P): greater than 0 weight % and less than or equal to 0.02 weight %; sulfur (S): greater than 0 weight % and less than or equal to 0.01 weight %; aluminum (Al): greater than 0 weight % and less than or equal to 0.1 weight %; nitrogen (N) : greater than 0 wt. % and less than or equal to 0.01 wt. %; at least one of titanium (Ti), niobium (Nb) and vanadium (V): greater than 0 wt. % and less than or equal to 0.1 wt. %, and the rest being Fe and other inevitable impurities; and a galvanized layer formed on the base steel, wherein the surface layer of the base steel in contact with the galvanized layer has a single-phase ferrite microstructure, the thickness of the decarburized layer formed on the surface layer of the base steel is 18 μm or greater, and the microstructure of the base steel includes 0% to 40% (including 0%) of ferrite, 10% to 30% of retained austenite, and the rest being martensite.

[0117] For example, when the tensile strength of the steel plate material finally produced is 980 MPa to 1180 MPa, the composition of the microstructure of the base steel may be 20% to 40% ferrite, 10% to 30% retained austenite, and the remainder martensite.

[0118] For example, when the tensile strength of the steel plate material finally produced is 1180 to 1470 MPa, the composition of the microstructure of the base steel may be 5% to 25% ferrite, 10% to 30% retained austenite, and the remainder martensite.

[0119] For example, when the tensile strength of the steel plate material finally produced is 1470 MPa or higher, the composition of the microstructure of the base steel may be 0% to 10% (including 0%) of ferrite, 10% to 30% of retained austenite, and the remainder of martensite.

[0120] The applicable welding current range for galvanized steel sheets is 6.0 kA to 7.5 kA. When welding galvanized steel sheets, it is characterized by a 0% probability of liquid metal embrittlement (LME) (i.e. the zinc coating melts and penetrates the surface of the base steel, causing embrittlement).

[0121] The finally produced steel plate material has a yield strength of 600 MPa or more, a tensile strength of 980 MPa or more, and a total elongation of 10% or more.

[0122] The product of tensile strength and total elongation of the final material is about 26,500, which is usually more than 25,000, which is generally regarded as the product of tensile strength and total elongation of high formability steel sheets of this strength level. It can be inferred that it has better formability than existing ultra-high strength steels of the same strength.

[0123] Figure 3 A photograph showing the appearance of liquid metal embrittlement cracks occurring in a galvanized steel sheet as a comparative example of the present invention is shown.

[0124] When spot welding is performed on a typical galvanized steel sheet on an automobile assembly line, the zinc coating melts and the molten metal zinc penetrates into the interface of the residual austenite in the base steel surface layer of the galvanized steel sheet, which may cause liquid metal embrittlement (LME). Due to this liquid metal embrittlement (LME) phenomenon, liquid metal embrittlement cracks (LME cracks) occur and the welding strength drops sharply. Therefore, there is a problem of a narrowing of the weldable current range. That is, when spot welding (resistance spot welding) is performed on ultra-high strength galvanized steel sheets, in the case of molten galvanized steel sheets (GI), the melting point of the coating layer is very low (420°C), and in the case of alloyed galvanized steel sheets, molten metal zinc is formed due to the peritectic reaction at around 780°C. The molten metal zinc formed penetrates along the grain boundaries of the base material into the area where the welding electrode is loaded at high temperature, so the strength of the base material decreases rapidly. Reference Figure 3 , it can be confirmed that zinc diffused toward the base material around the liquid metal embrittlement crack (LME crack) transforms austenite into αFe(Zn) at high temperature. Since αFe(Zn) is a very brittle material, this phase transformation further accelerates the embrittlement of the steel sheet. Therefore, as the amount of retained austenite increases, the frequency of occurrence of liquid metal embrittlement (LME) becomes more sensitive, and it is confirmed that a method of avoiding the presence of austenite in the surface layer can improve weldability.

[0125] In the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to an embodiment of the present invention, the phase fraction of the steel sheet is controlled by the developed alloy composition and the subsequent heat treatment (annealing / cooling / reheating) process, and the austenite phase formed in the current developed composition and annealing step is transformed into martensite / bainite or remains as austenite during the cooling process and reheating process in the subsequent heat treatment, thereby producing a composite phase.

[0126] Figure 4 An outline of a decarburization reaction in a method for producing an ultra-high strength galvanized steel sheet according to an embodiment of the present invention is shown.

[0127] If the temperature formed in the above annealing step is a region where an austenite phase is formed, but the dew point temperature of the atmosphere in the annealing furnace is increased to -10°C or higher, carbon as an austenite stabilizing element is oxidized on the surface of the base steel 10 and volatilized in the form of carbon monoxide, so that the decarburization reaction can proceed by a continuous reaction. This reaction can be represented by the following formula 1:

[0128] <Formula 1>

[0129] C(s)+H 2 O(g)→CO(g)+H 2 (g)

[0130] If the surface layer is depleted of carbon due to continuous decarburization reaction, and austenite in the surface layer has also been transformed into ferrite during the annealing step, austenite is not formed in the surface layer during the subsequent cooling / reheating step, and a single-phase ferrite structure can be ensured even at room temperature in the final step. Austenite that is sensitive to LME cracks can be avoided by the single-phase ferrite structure formed on the surface layer, thereby expanding the weldable current range and improving the welding strength.

[0131] Experimental Examples

[0132] Preferred experimental examples are given below to help understand the present invention. However, the following experimental examples are only used to help understand the present invention, and the present invention is not limited to the following experimental examples.

[0133] Table 1 shows the composition of the ultra-high strength cold-rolled steel sheet according to the experimental example of the present invention, and Table 2 shows the process conditions of the ultra-high strength cold-rolled steel sheet according to the experimental example of the present invention.

[0134] [Table 1]

[0135] Element C Si Mn P S Al Ti+Mo+Nb content 0.15 2.0 2.5 0.01 0.003 0.03 0.03

[0136] [Table 2]

[0137]

[0138] Steel having the composition (unit: weight %) of Table 1 was prepared, and a hot rolled steel sheet manufactured by a predetermined hot rolling process was prepared. The examples and comparative examples all had the same alloy composition. Referring to Table 2, the conditions of the hot rolling process were as follows: reheating temperature: 1200°C, finishing exit temperature: 900°C, coiling temperature: 600°C. After the cold rolling process, the process conditions were as follows: annealing temperature: 850°C, slow cooling temperature: 700°C, rapid cooling temperature: 250°C, reheating temperature: 460°C.

[0139] First Experimental Example

[0140] The first experimental example of the present invention realizes 1200MPa Q&P steel by applying the composition of Table 1 and the process conditions of Table 2, and then forms a hot-dip galvanized (GI) steel sheet by hot-dip galvanizing, and then performs a Griebe test (700 to 900°C). The test conditions are as follows: heating rate: 500°C / s, retention time: 1 second, deformation rate: 30mm / s.

[0141] Table 3 shows whether liquid metal embrittlement (LME) occurs in the ultra-high strength cold-rolled steel sheet according to the first experimental example of the present invention depending on the dew point. The dew point in Table 3 refers to the dew point depending on the moisture concentration in the annealing furnace, the normal dew point refers to the dew point below -45°C (for example, -50°C), and the high dew point refers to the dew point of 0°C. In addition, the temperatures of 700°C, 750°C, 800°C, 850°C and 900°C represent the Glebe test temperatures, the "LME" item indicates that the liquid metal embrittlement (LME) phenomenon occurs, and the "No LME" item indicates that the liquid metal embrittlement (LME) phenomenon does not occur.

[0142] [Table 3]

[0143] category 700℃ 750℃ 800℃ 850℃ 900℃ Normal dew point LME LME LME LME LME High dew point No LME No LME No LME LME LME

[0144] Figures 5 to 7 The first experimental embodiment of the present invention is shown in which, under the conditions of 800°C Glebe test temperature and normal dew point (DP<-45°C), a cross section of the steel surface layer, elongation test evaluation results and a photograph of the occurrence of liquid metal embrittlement (LME) cracks are shown. In addition, Figures 8 to 10 The figures respectively show the cross section of the steel surface layer, the elongation test evaluation results and the occurrence of liquid metal embrittlement (LME) cracks under the conditions of 800°C Glebe test temperature and high dew point (DP 0°C) in the first experimental embodiment of the present invention. Figures 5 to 7 As shown in Table 3, it can be confirmed that the single-phase ferrite microstructure does not appear on the surface layer of the base steel in contact with the galvanized layer, and liquid metal embrittlement cracks (LME cracks) appear, which reduces the elongation. Figures 8 to 10As well as Table 3, it can be confirmed that a single-phase (α) ferrite microstructure appears on the surface layer of the base steel in contact with the galvanized layer, and liquid metal embrittlement cracks (LME cracks) do not occur, thereby improving the elongation characteristics.

[0145] Second Experimental Example

[0146] Table 4 relates to the second experimental example of the present invention, which shows that the thickness of the decarburized layer and the occurrence of liquid metal embrittlement (LME) depend on the annealing time and annealing moisture in the alloyed hot-dip galvanized steel sheet achieved by applying the composition of Table 1 and the process conditions of Table 2. In the second experimental example, the alloying temperature of the galvanizing treatment is 530° C. In the case where the dew point is +15° C. or higher, problems such as corrosion of equipment in the annealing furnace may occur, and therefore it is excluded from the experimental examples.

[0147] [Table 4]

[0148]

[0149]

[0150] Fig.11 The positive square root (A) of the annealing time (A) in the annealing furnace according to the second experimental embodiment of the present invention is shown. 1 / 2 ) multiplied by the natural logarithm of the reciprocal of the water concentration (B) (ln(1 / B)), Fig.12 It is shown that according to the second experimental example of the present invention, the thickness of the decarburized layer formed on the surface layer of the base steel depends on the annealing time (A) and the moisture concentration (B) in the annealing furnace, Fig.13 The second experimental example of the present invention shows that the occurrence rate of liquid metal embrittlement (LME) depends on the annealing time (A) and the moisture concentration (B) in the annealing furnace. Fig.11 In the table, the unit of annealing time (A) is seconds (s), and the unit of water concentration (B) is ppm. Figures 11 to 13 It can be confirmed that when the annealing step is performed under the conditions where the annealing time (A) and the moisture concentration (B) in the annealing furnace satisfy the following formula 1 (Examples 1 to 6), i) the possibility of liquid metal embrittlement (LME) (occurs when the galvanized layer melts and penetrates into the surface of the base steel during welding of galvanized steel sheets, resulting in embrittlement) is 0%, and ii) the thickness of the decarburized layer formed on the surface layer of the base steel is 18 μm or greater.

[0151] <Formula 1>

[0152] (A) 1 / 2 x ln(1 / B)≤-65

[0153] In contrast, it was confirmed that when the annealing step was performed under the conditions where the annealing time (A) and the moisture concentration (B) in the annealing furnace did not satisfy Formula 1 (Comparative Examples 1 to 7), i) the possibility of liquid metal embrittlement (LME) (occurring when the galvanized layer melts and penetrates into the surface of the base steel during welding of galvanized steel sheets, resulting in embrittlement) was high, and ii) the thickness of the decarburized layer formed on the surface layer of the base steel was less than 18 μm.

[0154] That is, it is confirmed that in the method for manufacturing ultra-high strength galvanized steel sheet with excellent weldability, annealing can be controlled so that as the annealing time (A) for annealing becomes shorter, the moisture concentration (B) in the annealing furnace increases; and annealing can be controlled so that as the moisture concentration (B) in the annealing furnace becomes lower, the annealing time (A) for annealing increases.

[0155] Therefore, when the cold-rolled steel sheet is annealed in an annealing furnace according to the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to one aspect of the present invention, the positive square root of the annealing time (A 1 / 2 ) and the natural logarithm of the inverse of the moisture concentration (ln(1 / B)) to control the annealing time (A) and moisture concentration (B) in the annealing furnace.

[0156] As mentioned above, the first parameter of Equation 1 is expressed as the positive square root (A) of the annealing time (A) 1 / 2 ) multiplied by the natural logarithm of the inverse of the moisture concentration (B) (ln(1 / B)), it can be said that it has important technical significance as a factor that can simultaneously and effectively control the decarburization layer thickness and the liquid metal embrittlement (LME) incidence rate in ultra-high strength galvanized steel sheets. For example, in Comparative Examples 3 and 6 and Examples 2 and 5, the positive square root of the annealing time (A) (A 1 / 2 ) is the same, but the decarburized layer thickness changes significantly with the change of the natural logarithm of the reciprocal value of the water concentration (B) (ln(1 / B)). In Examples 4 and 2 and Comparative Example 7, the natural logarithm of the reciprocal value of the water concentration (B) (ln(1 / B)) is the same, but the occurrence rate of liquid metal embrittlement (LME) increases with the positive square root of the annealing time (A). 1 / 2 ), so the decarburization layer thickness and the liquid metal embrittlement (LME) incidence cannot be effectively controlled simultaneously by annealing time (A) or water concentration (B). In this respect, the first parameter mentioned above has a causal relationship with the better effect and is not just another way of expressing the known performance, so it can be said to have technical significance.

[0157] Meanwhile, referring to Table 4, it can be confirmed that as the dew point becomes higher and the annealing time becomes longer, the decarburization amount increases and the ability to avoid liquid metal embrittlement (LME) is excellent. In order to improve liquid metal embrittlement (LME), it is necessary to ensure a decarburized layer thickness of 18 μm or more.

[0158] Third Experimental Example

[0159] In the third experimental example of the present invention, the composition of Table 1 and the process conditions of Table 2 were applied to realize 1200 MPa grade Q&P steel, and a hot-dip galvanized (GI) steel sheet was formed by hot-dip galvanizing, and then a spot welding process was adopted. The welding current was 0.5 kA lower than the spatter (sputtering) generation condition, and LME evaluation was performed.

[0160] Table 5 shows the conditions of the spot welding process according to the third experimental example, Fig.14 The results of applying the spot welding process according to the third experimental example are shown. Fig.14 In the specification, the dew point refers to the dew point depending on the moisture concentration in the annealing furnace, the normal dew point refers to the dew point below -45°C (for example, -50°C), and the high dew point refers to the dew point of 0°C.

[0161] [Table 5]

[0162] Welding control Electrode head Pressure applied Pulse number Welding time Keep Time DC Ф6mm 3.5kN 1 350ms 100ms

[0163] See Table 5 and Fig.14 , it is confirmed that in the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to the comparative embodiment of the present invention, the annealing treatment is performed at a dew point lower than -45°C and the applicable welding current range is 6.0kA to 6.5kA, while in the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to the embodiment of the present invention, the annealing treatment is performed at a dew point of 0°C and the applicable welding current range is 6.0kA to 7.5kA. Therefore, it can be confirmed that in the method for manufacturing an ultra-high strength galvanized steel sheet with excellent weldability according to the embodiment of the present invention, by suppressing the surface layer austenite phase that causes LME cracks in the welded part, the strength can be ensured even under existing welding conditions, and defects in the spot welding process can be suppressed by expanding the total weldable range.

[0164] The present invention has been described with reference to the embodiments of the present invention, but various changes or modifications may be made by those skilled in the art. As long as these changes and modifications do not exceed the scope of the present invention, they are all included in the scope of the present invention. Therefore, the scope of the present invention should be determined by the appended claims.

Claims

1. A method for manufacturing an ultra-high strength galvanized steel sheet having excellent weldability, the method comprising: Annealing of cold rolled steel sheets in an annealing furnace. Among them, based on the positive square root of the annealing time (A 1 / 2 ) and the natural logarithm of the inverse of the moisture concentration (ln(1 / B)) to control the annealing time (A) and moisture concentration (B) in the annealing furnace.

2. The method according to claim 1, wherein: The annealing is controlled so that the water concentration (B) in the annealing furnace increases as the annealing time (A) during which the annealing is performed becomes shorter.

3. The method according to claim 1, wherein: The annealing is controlled such that as the moisture concentration (B) in the annealing furnace becomes lower, the annealing time (A) for which the annealing is performed increases.

4. The method according to claim 1, wherein: In terms of weight percent, the cold-rolled steel sheet comprises carbon (C): 0.1 weight percent to 0.5 weight percent; silicon (Si): 1.0 weight percent to 3.0 weight percent; manganese (Mn): 1.5 weight percent to 3.5 weight percent; Phosphorus (P): greater than 0 wt% and less than or equal to 0.02 wt%; Sulfur (S): greater than 0 wt% and less than or equal to 0.01 wt%; Aluminum (Al): greater than 0 wt% and less than or equal to 0.1 wt%; Nitrogen (N): greater than 0 wt% and less than or equal to 0.01 wt%, and the rest is iron (Fe) and other unavoidable impurities.

5. The method according to claim 4, wherein: The annealing is performed at a temperature corresponding to a dual-phase range of austenite and ferrite, the annealing causes a decarburization reaction on the surface of the steel sheet, and thus the annealing involves transforming austenite present in a surface layer of the steel sheet into ferrite.

6. The method according to claim 4, wherein: The annealing is performed at an annealing temperature of 830°C to 900°C.

7. The method according to claim 5, wherein: The annealing is performed in an annealing furnace under the condition that the annealing time (A) and the moisture concentration (B) satisfy the following formula 1: <Formula 1> (A) 1 / 2 x ln(1 / B)≤-65。 8. The method according to claim 7, further comprising: After annealing, Primary cooling of the steel plate to a temperature of 600° C. or higher and lower than 800° C. at an average cooling rate of 1° C. / s to 20° C. / s; Secondarily cooling the steel plate to a temperature of 200° C. or higher and lower than 300° C. at an average cooling rate of 20° C. / s or higher; reheating the steel plate to 350°C to 490°C and holding for 100 seconds or less; and The steel plate is galvanized.

9. The method according to claim 8, wherein: A single-phase ferrite microstructure is formed on the surface layer of the steel sheet after the galvanizing treatment, and the thickness of the decarburized layer formed on the surface layer of the steel sheet is 18 μm or more.

10. The method according to claim 8, wherein: The applicable welding current range of the galvanized steel sheet is 6.0 kA to 7.5 kA.

11. An ultra-high strength galvanized steel sheet with excellent weldability, comprising: A base steel, wherein the base steel comprises, in weight %, carbon (C): 0.1 weight % to 0.5 weight %; silicon (Si): 1.0 weight % to 3.0 weight %; manganese (Mn): 1.5 weight % to 3.5 weight %; Phosphorus (P): greater than 0 wt% and less than or equal to 0.02 wt%; Sulfur (S): greater than 0 wt% and less than or equal to 0.01 wt%; Aluminum (Al): greater than 0 wt% and less than or equal to 0.1 wt%; Nitrogen (N): greater than 0 wt% and less than or equal to 0.01 wt%; the rest is iron (Fe) and other unavoidable impurities; as well as The galvanized layer formed on the base steel, wherein a single-phase ferrite microstructure is formed on the surface layer of the base steel in contact with the galvanized layer, and the thickness of the decarburized layer formed on the surface layer of the base steel is 18 μm or more, The microstructure of the base steel includes 0% to 40% ferrite, 10% to 30% retained austenite, and the rest is martensite.

12. The ultra-high strength galvanized steel sheet according to claim 11, wherein: The applicable welding current range of the galvanized steel sheet is 6.0 kA to 7.5 kA.